2022
DOI: 10.1101/2022.07.20.500756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stepwise recombination suppression around the mating-type locus in the fungusSchizothecium tetrasporum(Ascomycota, Sordariales)

Abstract: Recombination is often suppressed at sex-determining loci in plants and animals, and at self-incompatibility or mating-type loci in plants and fungi. In fungal ascomycetes, recombination suppression around the mating-type locus is associated with pseudo-homothallism, i.e., the production of self-fertile dikaryotic sexual spores carrying the two opposite mating types. This has been well studied in two species complexes from different families of Sordariales: Podospora anserina and Neurospora tetrasperma. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 109 publications
2
13
0
Order By: Relevance
“…Increasing intra-tetrad selfing also induces more heterozygosity and thus slightly reinforces the sheltering effect of the mating-type locus. This is consistent with the findings that, in fungi, ascomycetes that reproduce via outcrossing and live as haploids do not show evolutionary strata (Skinner et al, 1993, Zhong et al, 2002, Phan et al, 2003, Kuhn et al, 2006, Jin et al, 2007, Malkus et al, 2009) whereas pseudo-homothallic ascomycete fungi, living as dikaryotic and undergoing mostly intra-tetrad selfing, are those with evolutionary strata around their mating-type locus (Menkis et al, 2008, Hartmann, Duhamel, et al, 2021, Hartmann, Ament-Velásquez, et al, 2021, Vittorelli et al, 2022). In basidiomycetes also, the species with evolutionary strata are dikaryotic and automictic, e.g.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Increasing intra-tetrad selfing also induces more heterozygosity and thus slightly reinforces the sheltering effect of the mating-type locus. This is consistent with the findings that, in fungi, ascomycetes that reproduce via outcrossing and live as haploids do not show evolutionary strata (Skinner et al, 1993, Zhong et al, 2002, Phan et al, 2003, Kuhn et al, 2006, Jin et al, 2007, Malkus et al, 2009) whereas pseudo-homothallic ascomycete fungi, living as dikaryotic and undergoing mostly intra-tetrad selfing, are those with evolutionary strata around their mating-type locus (Menkis et al, 2008, Hartmann, Duhamel, et al, 2021, Hartmann, Ament-Velásquez, et al, 2021, Vittorelli et al, 2022). In basidiomycetes also, the species with evolutionary strata are dikaryotic and automictic, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, our findings show that a mating-type locus has a sheltering effect on nearby deleterious mutations, especially in case of selfing and automixis, which can then play a role in the evolution of recombination suppression near mating-compatibility loci (Antonovics and Abrams, 2004, Jay et al, 2022). This may contribute to explain why evolutionary strata of recombination suppression near the mating-type locus are found mostly in automictic (pseudo-homothalic) fungi (Menkis et al, 2008, Branco et al, 2017, Branco et al, 2018, Hartmann et al, 2020, Hartmann, Ament-Velásquez, et al, 2021, Foulongne-Oriol et al, 2021, Vittorelli et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungi with evolutionary strata are most often automictic, i.e. undergoing intra-tetrad selfing (Hartmann et al ., 2020; Vittorelli et al ., 2022). Theoretical models have suggested that this may be because automictic fungi are dikaryotic for most of their lifecycle, even in ascomycetes, thus allowing the sheltering of deleterious alleles (Jay et al ., 2022), and because automixis can prevent diploid selfing to purge deleterious mutations near mating-type loci (Antonovics & Abrams, 2004; Tezenas et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%